Hacking suburban social infrastructure: glitch subjects and queer practices of social reproduction - Bain, Alison L.; Sharp, B. Wiley (Urban geography, 2025)
Infrastructure - material and social - enables urban life for some people and not others. Unevenly distributed between centers and peripheries, it affords differential capacities for action and shapes regimes of social reproductive labor. This paper explores Toronto's queer suburbanisms, foregrounding the lives of LGBTQ+ suburbanites who have been epistemically erased by urban geographies that discount sexuality and geographies of sexuality that overlook the suburban. It inductively analyzes 192 images from 19 photo-elicitation interviews conducted in the peripheral municipalities of Ajax, Markham, Mississauga, and Brampton in Canada's largest city-region, Toronto. It shifts attention away from object-centric notions of social infrastructure to prioritize its public social reproductive dimensions and affordances. In turn, it argues that LGBTQ+ suburbanites can be "glitch" subjects that "hack" suburban social infrastructure of homes, public parks, social venues, and public and private transportation, to afford the capacity for queer and trans public life to persist. Broader coalitions are still needed to unbuild cisheteronormative infrastructure and transform city-regional infrastructural landscapes. These quiet political gestures, however small, are nevertheless meaningful attempts to imagine yet-to-be-built suburban worlds.